HUBUNGAN RUTINITAS SHALAT DHUHA DENGAN PENURUNAN TINGKAT STRES PADA MUSLIMAH LANSIA - ADE NOVI FRESILA LUBIS; ELMAN BOY (LP2MTBM MAKARIOZ, 2021)
The increase in the number of elderly people (elderly) is followed by the appearance of various problems, such as adecrease in the physiological function of the aging process so that non-communicable diseases occur in the elderly. Prayeris a solid refuge in the face of various difficulties. When praying a person will feel calm and relaxed, so that the stressresponse decreases, and stimulates the anterior pituitary, inhibiting the adrenal cortex so that blood pressure decreases.The purpose of this study was to see the relationship between dhuha prayer routines and a reduction in stress levels inelderly Muslim women. The type of research used in this study is a descriptive-analytic study that aims to see therelationship between the Duha prayer routine and stress on elderly Muslim women, with a cross sectional study design.Sampling using a total sampling that can be done 30 people. Based on the age, the majority of elderly Muslim women were60-70 years old (64%). Based on the Duha prayer routine, the most elderly people pray Duha regularly (100%). Based onthe stress level, most elderly Muslim women were in the mild stress category (51%). There was a significant relationshipbetween the Duha prayer routine and a reduction in stress levels in elderly Muslim women p = 0.022 (p = 0.05). There is asignificant relationship between the Duha prayer routine and a reduction in stress levels in elderly Muslim women.